Using Problem-Based Learning to Promote Students’ Critical Thinking and Mathematical Problem-Solving Skills - Zetriuslita, Zetriuslita; Suripah, Suripah; Ariawan, Rezi; Hidayat, Riyan (FKIP Universitas Lampung, 2023)
Using Problem-Based Learning Models to Promote the Development of Students’Critical Thinking and Mathmatical Problem-Solving Skills and Their Level of Mathematical Curiosity. Objectives: This study aims to determine the ability to think critically and solve mathematical problems in terms of the level of mathematical curiosity of students by using the Problem-Based Learning model. Methods: The method of research is quasi-experimental with the mixed method with a sequential explanatory strategy. Findings: The results obtained sig = 0.002 < α, Ho rejected for mathematical critical thinking and sig = 0.049 < α, Ho rejected for problem solving abilities of students, and based sig > α, Ho received. Conclusion: There were differences in the mathematical critical thinking and problem solving abilities of students who received learning through the Problem-Based Learning model and conventional learning, but there is no difference based on the level of mathematical curiosity. Information was obtained from interviews, students prefer conventional learning, because complex analytical material requires more explanation and there are problems with lectures which are held during the day. Keywords: problem-based learning, critical thinking, mathematical problem solving, mathematical curiosity, mixed method, sequential explanatory strategy.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202311